Unique structural and ligand-binding properties of the Staphylococcus aureus serine hydrolase FphE - Jeyun Jo; Tulsi Upadhyay; Xiangyan You; John M. Bennett; Hyunbin Lee; Matthew Bogyo; Matthias Fellner (Proceedings of the National Academy of Sciences, 2026)
Staphylococcus aureus is a human pathogen capable of forming biofilms that complicate treatment and facilitate chronic infections. A family of S. aureus serine hydrolases are important regulators of virulence and biofilm formation. Among these, FphE is highly specific to S. aureus and therefore a viable target for both imaging and therapy. Here, we present bioinformatic and structural evidence that FphE may be involved in aromatic compound metabolism. In addition, 12 distinct crystal forms reveal that FphE exists as a highly unusual but stable and flexible, cross-subunit homodimer, unique to the large alpha/beta hydrolase superfamily. Substrate engagement favors retention of the dimeric state, which is a more catalytically active form of the enzyme, and small-angle X-ray scattering confirms that the dimeric architecture occurs in solution. High-resolution cocrystal structures of FphE covalently bound to two chemically distinct ligands reveal different modes of active site engagement, supporting an atypical structural plasticity of the dimer interface. Together, these findings establish FphE as a structurally unique alpha/beta hydrolase and provide a foundation for structure-guided development of S. aureus –specific inhibitors and imaging probes.